STUDI KELAYAKAN BISNIS PENDIRIAN USAHA AGRIBISNIS “CV TIRAM SEJAHTERA MANDIRI” - Rizaldi, Irvan Zaulhan; Nuzulia Khoiriyah (JOURNAL SAINS STUDENT RESEARCH, 2026)
The continuously increasing annual demand for oyster mushroom commodities necessitates the availability of high-quality, sterile, and consistent seeds. However, poor seed quality due to suboptimal sterilization processes often becomes the main factor in the failure of local farmers' cultivation. This study aims to analyze the feasibility of establishing an oyster mushroom seed production business (F0, F1, and F2) at CV Tiram Sejahtera Mandiri from various business design perspectives. The increasing demand for oyster mushrooms directly impacts the need for high-quality mushroom seeds. The design results indicate that the business location in Balong, Karanganyar, has highly supportive geographical conditions for operations. From a technical aspect, the production process is designed using high-temperature sterilization technology (autoclave) and aseptic inoculation with laminar air flow to ensure contamination-free seed quality. The marketing strategy focuses on segmenting mushroom farmers in the Solo Raya area through an educational approach and cultivation consulting services. The research methodology encompasses a comprehensive analysis of juridical, market, technical, managerial, environmental, and financial aspects. Managerially, this business implements strict Standard Operating Procedures (SOPs) at every production stage to maintain product quality consistency. This study provides strategic recommendations for the development of agribusiness SMEs to sustainably increase the productivity of the horticulture sector. Considering the existing challenges and Opportunities, establishing an oyster mushroom seed production business is a strategic step to support local food security and improve farmer welfare. With appropriate production technology, strict quality control, and professional service, Fresh Mushroom is expected to become a trusted provider of oyster mushroom seeds.